Consideration of Mandibular Third Molar Extraction for Post-Orthodontic Relapse Prevention - Narmada, Ida Bagus; Alida, Alida; Primadewi, Theresia (Indonesian Journal of Dental Medicine, 2022)
Background: Orthodontic treatment may result in undesired teeth movement which is called "relapse”. One of the factors thought to influence post-orthodontic treatment relapse is the third molar, especially mandibular third molar it's because third molar eruption and mandibular anterior crowding occur simultaneously. The extraction of this teeth can be suitable prevention of tooth relapse after orthodontic treatment. Purpose: This study aimed to describe whether there is an effect of mandibular third molar extraction on relapse in post-orthodontic treatment crowding cases so that it can determine whether this action can be a preventive solution in these cases. Review: This review was conducted by studying total 11 journals (n = 2/11) mentioned that there was third molar relation to the anterior crowding teeth and most likely recommended its extraction to prevent relapse post- orthodontic treatment. Meanwhile (n = 8 / 11) did not agree with the statement, and (n= 1/11) is still undetermined. Conclusion: Extraction of the mandibular third molar can prevent crowding relapse, in case of impaction it must be extracted, and this extraction can be performed before, during, or after orthodontic treatment.